MAKNA PICTORIAL HEALTH WARNING PADA KEMASAN ROKOK DALAM MENGOMUNIKASIKAN PESAN BAHAYA MEROKOK - Samosir, Deborah Sondang Napita; C. Priyatna, Centurion; Hafiar, Hanny (Jurnal Nomosleca, 2019)
Abstract Pictorial Health Warning (PHW) is one of the communication media of the Ministry of Health of Indonesia to provide information and raise awareness in Indonesia about the health effects of smoking. In fact, PHW versions of those who were smoking next to a small child can not be interpreted by the public so that the message to be conveyed by the Indonesian Ministry of Health through the PHW can not be received well. The Charles Sanders Peirceâ€™s semiotic analysis aims to assess the significance of the PHW version of the smoke in addition to a small child in communicating the dangers of smoking message. The analysis showed that there are three main symbol that can construct messages dangers of smoking, that if a person smokes near loved ones, he poisoned the people they love. Keywords : PHW, cigarette, semiotics, PeirceDOI :Â https://doi.org/10.26905/nomosleca.v5i1.2750